Antimicrobial effects of XF drugs against Candida albicans and its biofilms - Board-Davies, E. L.; Rhys-Williams, W.; Hynes, D.; Love, W. G.; Williams, D. W. (Frontiers in Fungal Biology, 2023)
Compared with antibiotics for treating bacterial infections, there are a limited number of antifungal agents. This is due to several factors, including the difficulties of identifying suitable antifungals that target the fungal cell without damaging host cells, and the reduced rates of diagnosis of fungal infections compared with those caused by bacteria. The problem of treating fungal infections is exacerbated by an increasing incidence of antifungal resistance among human fungal pathogens. Three XF drugs (XF-73, XF-70, and DPD-207) have previously displayed innate bactericidal effects and a low propensity for microbial resistance, with XF-73 and XF-70 having a second, light-activated mechanism of action [known as photodynamic therapy (PDT)]. In an effort to expand the repertoire of antifungal agents, this research assessed the in vitro activity of XF drugs via both mechanisms of action against six strains of the fungal pathogen Candida albicans in both planktonic and biofilm cultures. In addition, this research examined the effects of XF drug treatment on biofilms of C. albicans in a reconstituted human oral epithelium model. All C. albicans strains tested were susceptible to XF-73 and XF-70, with minimum inhibitory concentrations (MICs) between 0.25 µg/mL and 2 µg/mL; DPD-207 was less potent, with MICs between 4 µg/mL and 16 µg/mL, and light activation did not enhance these MICs. Complete biofilm eradication was not reported at the tested XF drug concentrations. However, live and dead staining of C. albicans cells in biofilms after XF drug treatment demonstrated that XF-73 and XF-70 were active against most Candida biofilms tested from 64 µg/mL; again, light activation did not enhance anti-biofilm activity. Candida biofilms were more resistant to DPD-207, with fungicidal effects occurring from 256 µg/mL. XF-73 and XF-70 reduced penetration of C. albicans biofilm into reconstituted human oral epithelium (RHOE) and resulted in less damage (as determined by reduced lactate dehydrogenase release) than untreated biofilms. Overall, the results highlight the potential of XF drugs as new drugs for the management of topical infections caused by C. albicans. Further studies are warranted on the development of XF drugs as antifungals, particularly for XF-73 and XF-70.